2004
DOI: 10.1007/s00535-004-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary, solitary, adult T-cell leukemia / lymphoma of the descending colon

Abstract: We herein report a patient with adult T-cell leukemia/lymphoma (ATLL) of the descending colon. A 64-year-old man was admitted to our hospital complaining of left lower abdominal pain. Endoscopic examination revealed an ulcerative tumor in the descending colon that was diagnosed as T-cell lymphoma by biopsy. Neither distant organ metastasis nor lymph node swelling was observed by radiographic examinations. Curative excision with left hemicolectomy and regional lymph node dissection was performed. Surgical secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We targeted DNA instead of RNA, because RNA viral loads are extremely low, even in blood and progression to disease is measured by quantifying HTLV-1 proviral load in peripheral blood mononuclear cells ( Kuramitsu et al 2015 ). Moreover, several studies in humans infected with HTLV-1 and Indian rhesus macaques experimentally infected with a replicative form of HTLV-2 showed presence of the proviral DNA in the gastrointestinal tract and epithelial cells of asymptomatic patients ( Tokunaga et al 1993 ; Hidaka et al 2004 ). A study reporting on experimental infection of Indian rhesus macaques with HTLV-2 ( Gordon et al 2010 ), showed evidence of comparable levels of HTLV-2 DNA in blood, lymphoid tissues, and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…We targeted DNA instead of RNA, because RNA viral loads are extremely low, even in blood and progression to disease is measured by quantifying HTLV-1 proviral load in peripheral blood mononuclear cells ( Kuramitsu et al 2015 ). Moreover, several studies in humans infected with HTLV-1 and Indian rhesus macaques experimentally infected with a replicative form of HTLV-2 showed presence of the proviral DNA in the gastrointestinal tract and epithelial cells of asymptomatic patients ( Tokunaga et al 1993 ; Hidaka et al 2004 ). A study reporting on experimental infection of Indian rhesus macaques with HTLV-2 ( Gordon et al 2010 ), showed evidence of comparable levels of HTLV-2 DNA in blood, lymphoid tissues, and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows colonic involvement of ATLL reported in the English literature. In addition to the prior categories, tumor type [8,15] and colitis type [12] have been reported. A search of the MEDLINE database retrieved only 5 reported cases of ATLL with MLP [5,[9][10][11]13] .…”
Section: Discussionmentioning
confidence: 99%
“…A search of the MEDLINE database retrieved only 5 reported cases of ATLL with MLP [5,[9][10][11]13] . Although the molecular mechanisms which may influence phenotypes [8] 60/M ND Ulcerated tumor ND 15 mo, died Itsuno [9] 43/M Gastric ulcerated tumors MLP CPA, DXR, VCR 8 mo, died Gakiya [10] 62/M Duodenal MLP MLP CPA, PSL 1 mo, alive Isomoto [11] 70/M Duodenal polypoid tumor MLP CPA, DXR, VDS, VP-16 4 mo, alive Isomoto [12] 47/M Gastric protruding masses Granular, friable, and hyperemic mucosa CPA, DXR, VCR, PSL 12 mo, died Isomoto [13] 58/F Normal MLP CPA, DXR, VDS 7 mo, died Asada [14] 78/F ND Reddish, flat or slightly elevated lesion CPA, THP, VCR, VP-16 died Hidaka [15] 68/M ND Ulcerated tumor surgery, CPA, DXR, VDS, PSL 10 mo, alive Onishi [16] of colonic lesions have not been clarified, colonic MLP may be correlated with coexistence of upper gastrointestinal MLP or polypoid lesions (Table 1). In addition, patterns and degree of ATLL cell infiltration have been suspected to be reflected to the morphological differences [17] .…”
Section: Discussionmentioning
confidence: 99%